Resultados do uso da solução reveladora de linfonodos no estadiamento patológico do câncer colorretal - Magda Maria Profeta da Luz (2014)
The correct staging of colorectal cancer (CRC) has been considered a crucial prognostic feature, since it determines the most appropriate management of the patient and may lead to improved disease-free survival. One of the key parameters considered in the pathological staging is the number of retrieved lymph nodes in surgical specimens. It is known that the more nodes obtained, the greater the chance of being found metastases, changing the staging and promoting the indication of adjuvant therapy. The number of retrieved lymph nodes varies widely, often staying at a number below twelve, the minimum value to be obtained in surgical specimens of CRC. This study was designed to assess whether the use of a lymph node revealing solution would be able to increase significantly the number of nodes retrieved in specimens of CCR and change the pathological staging of the disease. The data from 780 surgical specimens of CRC were divided into two groups, the first with 497 specimens examined in the conventional way and the second group of 283 surgical specimens treated with revealing solution of lymph nodes. A median of 15 nodes retrieved was obtained in the onventional group, whereas in the group treated with the revealing solution, the number of lymph nodes obtained was 24 (p < 0.0001). It was also observed that the rate of specimens with less than 12 lymph nodes (pNx) decreased from 32.6 % in the conventional group to 9.2 % in the group with revealing solution. Consequently there was an increase in the number of pN0, pN1, pN2 and pN3 stages in the group using the revealing solution. This fact reflects improvement in pathological staging with its possible benefits related to the most appropriate indication of adjuvant therapy and better disease control. It was also observed that in cases of tumors located in the colon rather than the rectum, with larger surgical specimens and younger patients there is a higher potential for lymph node staging other than pNx. Data were also obtained in specimens of GSRL in which conventional dissection was done before the application of the solution with significant gain of dissected lymph nodes after applying the solution. Conventional dissection in this group was also significantly more efficient than that practiced in the GC. The use of lymph node revealing solution is able to increase the harvest of lymph nodes in surgical specimens of CRC, increasing the accuracy of pathological staging of the disease. Its use should be ntroduced more widely in the gastrointestinal pathology services.